1995
DOI: 10.1086/133562
|View full text |Cite
|
Sign up to set email alerts
|

The Keck Low-Resolution Imaging Spectrometer

Abstract: The Low Resolution Imaging Spectrometer (LRIS) for the Cassegrain focus of the Keck 10-m telescope on Mauna Kea is described. It has an imaging mode so it can also be used for taking direct images. The field of view in both spectrographic and imaging modes is 6 by 7.8 arcmin. It can be used with both conventional slits and custom-punched slit masks. The optical quality of the spectrograph is good enough to take full advantage of the excellent imaging properties of the telescope itself. The detector is a cooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
1,743
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,944 publications
(1,761 citation statements)
references
References 6 publications
6
1,743
0
Order By: Relevance
“…Chapman et al describe a population of 850µm-selected SMGs which have radio counterparts; these radio counterparts have astrometric precision <1 and provide excellent multi-slit spectroscopic targets. The Chapman et al sample of 73 galaxies was spectroscopically observed at Keck Observatory using the LRIS instrument (Oke et al, 1995) and has a median redshift of z = 2.2 (some of these redshifts had been reported in earlier works, e.g. Barger et al, 2000;Chapman et al, 2003b).…”
Section: Redshift Distributions Of 850µm-14 Mm-selected Dsfg Populatmentioning
confidence: 95%
“…Chapman et al describe a population of 850µm-selected SMGs which have radio counterparts; these radio counterparts have astrometric precision <1 and provide excellent multi-slit spectroscopic targets. The Chapman et al sample of 73 galaxies was spectroscopically observed at Keck Observatory using the LRIS instrument (Oke et al, 1995) and has a median redshift of z = 2.2 (some of these redshifts had been reported in earlier works, e.g. Barger et al, 2000;Chapman et al, 2003b).…”
Section: Redshift Distributions Of 850µm-14 Mm-selected Dsfg Populatmentioning
confidence: 95%
“…Palomar observations utilized the dualbeam Double Spectrograph on the 200-inch Hale Telescope, which was configured with the 1.5 arcsec wide slit, the 5500 Å dichroic, the 600 mm −1 grating on the blue arm (λ blaze = 4000 Å; spectral resolving power R ≡ λ/ λ ∼ 1200), and the 316 mm −1 grating on the red arm (λ blaze = 7500 Å; R ∼ 1800). Keck observations utilized the dual-beam Low Resolution Imaging Spectrograph (LRIS; Oke et al 1995) on the Keck I telescope, configured with the 1.5 arcsec wide slit, the 600 mm −1 grism on the blue arm (λ blaze = 4000 Å; R ∼ 800) and the 400 mm −1 grating on the red arm (λ blaze = 8500 Å; R ∼ 1000). All nights listed in Table A1 were photometric, and we processed the data using standard techniques within IRAF.…”
Section: A P P E N D I X a : S P E C T Ro S C O P I C O B S E Rvat I mentioning
confidence: 99%
“…In preparation for, and in support of, the NuSTAR observations, we also obtained optical spectroscopy of NGC 7674 using the Low Resolution Imaging Spectrometer (LRIS) on the Keck Telescope (Oke et al 1995). The observations were carried out on 2014 June 25 through a 1.0 arcsec wide slit, using both the blue (600 lines mm −1 ) grism and the red (400 lines mm −1 ) grating, with the D560 dichroic.…”
Section: Optical Spectroscopymentioning
confidence: 99%